2018
DOI: 10.1186/s12876-018-0755-5
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained chronic liver disease in Ethiopia: a cross-sectional study

Abstract: BackgroundHepatitis B virus (HBV) infection is assumed to be the major cause of chronic liver disease (CLD) in sub-Saharan Africa. The contribution of other aetiological causes of CLD is less well documented and hence opportunities to modulate other potential risk factors are being lost. The aims of this study were to explore the aetiological spectrum of CLD in eastern Ethiopia and to identify plausible underlying risk factors for its development.MethodsA cross-sectional study was undertaken between April 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…A post hoc sensitivity analysis was performed excluding all cases of CLD with an identifiable etiology after a comprehensive panel of tests, which included parasitology and serological testing for viral, autoimmune, and genetic liver diseases . Controls did not undergo the same comprehensive panel of tests or abdominal ultrasound, but all had serum ALT activities <40 U/L and were screened for the risk factors assumed a priori to be the most relevant ( viz .…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A post hoc sensitivity analysis was performed excluding all cases of CLD with an identifiable etiology after a comprehensive panel of tests, which included parasitology and serological testing for viral, autoimmune, and genetic liver diseases . Controls did not undergo the same comprehensive panel of tests or abdominal ultrasound, but all had serum ALT activities <40 U/L and were screened for the risk factors assumed a priori to be the most relevant ( viz .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Khat chewing is also associated with a number of somatic health sequelae, including myocardial infarction, systemic hypertension, upper gastrointestinal cancers, cognitive impairment, and impaired fetal growth . Khat has also been implicated in the development of both acute hepatitis and chronic liver disease (CLD) in several case series. Chapman et al reported on 6 patients of Somali origin, living in the United Kingdom, in whom khat abuse was implicated in the development of fulminant hepatic failure .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…38 45 Khat chewing (a popular recreational drug in some settings) was recently found to be a major cause of unexplained liver disease in east Ethiopia. 45 Aflatoxin exposure is associated with liver cirrhosis and is among the major causes of hepatocellular carcinoma globally, with most cases reported from sSA. Within a previous study of the GPC,>90% of individuals had evidence of exposure.…”
Section: Open Accessmentioning
confidence: 99%
“…1 The understudied nonalcoholic fatty liver disease probably has a role in these latter cases, considering the increase in obesity in sub-Saharan Africa, and traditional herbal medicine could also contribute, because its use is associated with a substantial increase in liver fibrosis. 2,3 Treatment of liver cirrhosis is inaccessible in most parts of sub-Saharan Africa, given the huge shortage of hepatologists and gastroenterologists, interventional radiologists, hepatobiliary surgeons, and pathologists. Liver transplants are uncommon and done only in South Africa, and the costs are prohibitive for the governments of almost all sub-Saharan countries.…”
Section: Liver Cirrhosis In Sub-saharan Africa: Neglected Yet Importantmentioning
confidence: 99%